RUSSIAN AND INTERNATIONAL EXPERIENCE OF REGINAL ECONONMIC CAPACITY INDEX FORMATION - Oksana V. Shulaeva; Mihail A. Esenin; Eduard A. Agekjan (Статистика и экономика, 2016)
The article analyses the term “regional economic capacity” and Russian andinternational approaches to formation of regional economic capacity index.The paper presents a synthesis of the indicators and their consolidatedthematic groups that are used to assess the regional economic capacityand examines the possibility of using estimates of economic capacity andits performance in monitoring the development of small business in theRussian regions.